Molecular identification of blaTEM gene of extended-spectrum beta-lactamase-producing Escherichia coli from healthy pigs in Malang district, East Java, Indonesia - Effendi, Mustofa Helmi; Hartadi, Erwan Budi; Witaningrum, Adiana Mutamsari; Permatasari, Dian Ayu; Ugbo, Emmanuel Nnabuike (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The increase and prevalence of multidrug-resistant bacteria in livestock animals are serious public health concerns. This study aimed to identify the presence of the blaTEM gene in extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli isolated from rectal swabs of apparently healthy pigs in Malang District, East Java, Indonesia. Materials and Methods: A total of 120 rectal swab samples were collected from the pigs. The rectal swabs were screened for the presence of E. coli using standard microbiological identification procedures. The Kirby–Bauer disk diffusion method identified multidrug-resistant E. coli. Five different classes of antibiotics were used to identify multidrug-resistant isolates, including Ciprofloxacin, Trimethoprim, Tetracycline, Streptomycin, and Aztreonam. Multidrug-resistant E. coli isolates were characterized for the presence of ESBL using double-disk synergy test methods. The presence of blaTEM genes was determined using polymerase chain reaction methods. Results: The results of this study indicated that 107 (89.2%) out of 120 samples analyzed were positive for E. coli isolates. A total of 32 (29.9%) E. coli isolates were identified to be multidrug-resistant and further subjected to molecular testing. The molecular analysis revealed (5; 15.6%) E. coli isolates to harbor the blaTEM gene. Conclusion: The results of this study revealed that pigs and products of pork origin must be considered a source of transmission of ESBL-producing E. coli to public health important under the food chain. J. Adv. Vet. Anim. Res., 9(3): 447–452, September 2022 http://doi.org/10.5455/javar.2022.i613